Physical fitness and physical activity level in school going adolescent children - Nagrale, Sanket; Jiandani, Mariya; Mehta, Amita (International Journal Of Community Medicine And Public Health, 2020)
Background: Adolescence is transitional phase between childhood and adulthood characterized by marked acceleration in growth. The objective of this study was to evaluate differences between the boys and girls in physical fitness and the variation in their physical activity at school going children at Pune. Methods: The study was carried out at various schools in Pune city. Government, government aided (semi government), and private schools were selected according to different zones of the city using random sampling method. A self-administered youth physical activity questionnaire (Y PAQ) has been given for testing their level of physical activity. Physical fitness test such as curl-up test, 90° push-up test, trunk lift, back saver sits, and reach test were performed for analysing the physical fitness of the students. Results: A total of 296 students, 142 boys (aged 13.47±0.04 years) and 154 girls (aged 13.40±0.03 years) were included in the study. The average/mean comparison demography between boys and girls for curl-up test showed 21.61±10.00 and 15.21±7.24 repetitions/min respectively. The average of 900 push-ups test between boys and girls were 12.72±7.31 and 5.12±3.25 repetitions/min respectively. The average/mean of Trunk lift test was 5.67±2.56 in boys and 5.12±2.45 inches in girls respectively. Conclusions: The study concluded that there was lower fitness level as per calculation of healthy fitness zone seen amongst the school going children and also there were lower levels of their physical activity in day to day life. Also, study results show significant difference among the boys and girls in their physical fitness level.